The impact of environmental and behavioural cofactors on the development of cervical disorders in HR-HPV-infected women in Serbia. Issue 13 (20th June 2018) - Tasic, D.; Lazarevic, I.; Knezevic, A.; Tasic, L.; Pikula, A.; Perisic, Z.; Jovanovic, T.; Cupic, M.
Abstract: Persistent infection with one or more highly oncogenic human papillomaviruses (HPVs) or high-risk-HPV (HR-HPV) is necessary but not a sufficient aetiological agent for the development of cervical neoplasia. A number of viral, host, environmental and behavioural factors are suggested to be associated with the progression of cervical disorder. This study aimed to evaluate the impact of environmental and behavioural cofactors on the development of cervical disorders in HR-HPV-infected women in Serbia. A total of 541 women have been tested by PCR for the presence of HPV on the cervix. HPV genotypes were determined by direct DNA sequencing. Women identified as HR-HPV-positive were further classified into four subgroups according to their cytological status. All relevant information about demographical and behavioural factors was obtained by interviewer-based questionnaire. A number of analytical and descriptive statistical methods were used for processing the data. The cofactors found to be of significance for the progression of cervical disease were older age, body mass index >25, lower educational level, long-term smoking, previous genital infections and cervical interventions. On the other hand, condom use was found to have a protective role. Information about these cofactors might be very important for the development of more efficient cancer prevention programmes and promotion of anti-HPV vaccination.